2022
DOI: 10.1039/d2cp00439a
|View full text |Cite
|
Sign up to set email alerts
|

Decoding hexanitrobenzene (HNB) and 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) as two distinctive energetic nitrobenzene compounds by machine learning

Abstract: Energetic materials (EMs) are a group of special energy materials, and it is generally full of safety risk and generally costs much to create new EMs. Thus, the machine learning...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Recently, Zhang's group has reported a combination study of theoretical calculations and machine learning and found that moderate energy content and extremely high safety of TATB basically stem from its face-to-face π-stacking mode that facilitates enhanced molecular stability compared to other ∼370 000 000 single ring-containing aromatic compounds. 82…”
Section: π–π Interactions In Various Types Of Energetic Crystalsmentioning
confidence: 99%
“…Recently, Zhang's group has reported a combination study of theoretical calculations and machine learning and found that moderate energy content and extremely high safety of TATB basically stem from its face-to-face π-stacking mode that facilitates enhanced molecular stability compared to other ∼370 000 000 single ring-containing aromatic compounds. 82…”
Section: π–π Interactions In Various Types Of Energetic Crystalsmentioning
confidence: 99%
“…5 Nowadays, the big data-driven molecular design becomes increasingly popular with the further enhancement of efficiency, and numerous fuel molecules and energetic molecules with excellent properties have been designed and synthesized. 6–9…”
Section: Introductionmentioning
confidence: 99%
“…For example, the combination of the SMILES codes of various groups and frames enables us to produce a large number of molecules in no time for subsequent high throughput calculations. 6 In general, a larger part of the combination is ineffective, i.e. , most of these molecules cannot be potential candidates.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the high requirement of DFT to the computation resource, it is infeasible to use DFT to explore huge unknown compound space. Recently, machine learning (ML), as a key technique of artificial intelligence, has been increasingly popular in accelerating the discovery of novel functional materials and pharmaceutical materials, including the cocrystal materials. It is noted that previous ML applications on the cocrystals mainly focused on the classification task to screen a possible pair of coformers to form cocrystals. , However, successful cocrystal design requires not only to quickly screen the potential coformer pair but also to know whether the cocrystal can achieve desired properties.…”
Section: Introductionmentioning
confidence: 99%